Core capabilities of Chinese centers for disease control and prevention public health personnel: a network analysis from Northeast China - Yuxuan Wang; Ruiqian Zhuge; Kexin Wang; Nan Meng; Weiqi Huang; Yingxin Wang; Honghao Zhang; Xin Zhang; Qunkai Wang; Shanshan Gao; Yunxia Ma; Huan Liu; et al. (BMC Medical Education)
Abstract Background The COVID-19 pandemic has highlighted the continued inadequacy of the capability of Center for Disease Control and Prevention (CDC) public health personnel to respond effectively to emerging infectious disease outbreaks, as well as the urgent need for specific tools to assess the capability needed by CDC public health personnel in the post-pandemic era. Using network analysis, we aimed to analyze the comprehensive capacities of CDC public health staff and the relationships between these capacities. We also examined the impact of standardized public health training on their capacities and provided actionable recommendations for improving their training and overall capability. Methods This study employs a cross-sectional design. A self-developed questionnaire was used to evaluate the capabilities of public health personnel in CDC. Network analysis was conducted using the qgraph package in R (version 4.3.1) to construct a capability network model, while the bootnet package ensured the stability and reliability of the network through bootstrapping. The NetworkComparisonTest package was applied to compare network structures and identify differences between groups. Results Over half (51.80%, N = 11,912) of public health personnel rated their comprehensive capabilities as poor. Core capabilities, including research, motivation, and emergency response, were identified as pivotal within the capability network. The network stability coefficient for strength was 0.75, indicating reliable results. The capability networks of those who participated in standardized training differed significantly from those who did not (P = 0.04). Conclusion CDC public health personnel exhibit significant capability gaps, particularly in research and leadership. Standardized training provides some benefits but remains insufficient. Policymakers should address these gaps by aligning training content with critical capability needs, offering flexible and targeted training methods (e.g., virtual courses, self-paced modules), and implementing capability-based assessments to evaluate training outcomes.